POLITIK AUSTRALIA DALAM FRAMEWORK CONVENTION ON TOBACCO CONTROL (FCTC) PADA PEMERINTAHAN JULIA GILLARD (2010-2013) - Sri Yulianti; Tri Joko Waluyo (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2014)
This  research will focus on the Australian Policy in the implementation of the Framework Convention on Tobacco Control (FCTC) in the era of the Prime Minister Julia Gillard.  The FCTC which provides a framework for international cooperation to address the global health crisis caused by tobacco,The period time used in this research is within 2010 until 2013 that is period Julia Gillard served as Prime Minister of Australian. This study used a qualitative research method that the source data is taken from books, journals, newspapers, the internet, and previous research. Perspectives and levels of analysis used in this study is that the individual as the main actor. By using a perspective behavioralism, the theory of  decision making in  foreign policy analysis by James N. Rosenau, will describe the direction of the object of analysis.  The result of this research is the implementation of the Australian tobacco control policy relevant treaty obligations undertaken by Parties to the WHO FCTC, with finds out the things which causes Australian tobacco control policy under the of the Prime Minister Julia Gillard to be aggressive in world, like  Julia Gillard  success  makes  the Tobacco  Plain  Packaging  lawsis  the first  policy  in the history of  the world. Although  major  tobacco companies  refuse  the Tobacco Plain Packaging  policy,  Julia Gillard  is committed to implement  measures of the Australian tobacco control policy to be progressive have been made by the states and territories of Australia.Keywords : Australian Tobacco control Policy, FCTC, Behavioralism